Investigation of Oxidative Stress in Patient with Varicella Zoster Virus (VZV) Infection - Nisreen Kaddim Radi (Journal of Global Pharma Technology, 2017)
Varicella zoster virus (VZV) is a member of the eight known herpes virus that infect humans. VZV infection is specific to humans. It causes chickenpox (varicella), the most common disease affecting children, adolescents, young adults and herpes-scale (shingles) in the elderly; shingles are rare in children. In direct immune flourescens assay for determination of antibodies IgG/IgM against varicella Zoster virus in the samples collected from patient serum show 98%positive result. The patients groups, had greater levels of SOD in contrast with control groups result at significant differences (P≤ 0.05) .Conclusion these results suggest that severity infection within vortesella zoster virus causes high level of sod.Keywords: Antitoxidant, Immuno flourescens, Zoster, varicella, Oxidative.